Representation of Jeans as a Form of Resistance in Jakarta Demonstrations 1970-1998 - Wibbiola, Shalfara; Bashori, Muzakki (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This research examines the role of jeans as a symbol of social resistance in student demonstrations in Jakarta in 1970-1998. Initially seen as an icon of modernity and globalization, jeans over time became an identity for students and activists who opposed the repressive policies of the New Order. During the 1974 Malari Demonstrations, students wore jeans as a form of criticism against economic dependence on foreign capital, and signaled their solidarity with workers affected by ongoing economic injustice. During the 1998 Reformation, jeans reappeared as a symbol of resistance against the Soeharto government, which was considered authoritarian and corrupt. This research uses a historical research method with a social history approach. The research process includes collecting data sources (heuristics), analyzing data validity (source criticism), interpreting the symbolic meaning of jeans, and compiling historical narratives (historiography). By referring to Sartono Kartodirdjo's concept of social history, the results of this study show that material culture, such as jeans, is not only part of the lifestyle, but also a form of political expression tool in the student movement. The existence of this research can confirm that clothing can also play a role in shaping collective identity and voicing aspirations for social change in society.